The Relationship Between Spiritual Intelligence and Empathy of Students - Mohamad Rizal Pautina; Moh. Rizki Djibran (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
The purpose of this research is to examine the relationship between spiritual intelligence and student empathy. Spiritual intelligence is a person's ability to assess, face and solve life problems and be able to behave in accordance with religious norms. Meanwhile, empathy is the ability to understand and feel the feelings of others. The research method used is a correlational method. The population in this study is a student of The Department of Guidance and Counseling Faculty of Education, Gorontalo State University which amounted to 336 people. The study sampled 168 students. The conclusion of this study is that there is a positive and significant relationship between spiritual intelligence and empathy of students of the Department of Guidance and Counseling, Faculty of Education, State University of Gorontalo.